Who owns English?: Interviews to the Indonesians - Nining Ismiyani (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
As English does not merely belong to its original speakers to mention Americans, British people, Canadians, Australians, or other first speakers of English but also to those speaking English as their second language such as Singaporeans, Malaysian, Indians and other second speakers of English which are now familiar with the terms ‘new varieties of English’, people’s perceptions and attitudes are ostensibly changing; from a way of thinking that speaking English must be like American English or British English to a new paradigm that speaking English should be intelligible and understandable. This study was aimed at delineating Indonesian people’s attitudes on the new paradigm of the English ownership at the current time.  This study applied the qualitative descriptive design. Three Indonesians with different backgrounds in terms of age generation, education, and residence were interviewed. The findings indicated that their attitudes towards English have positively changed towards the ownership of this global language. To conclude, English still holds its privilege as an International language, but the metaphor of who owns English is no longer a great issue.